Identification of immunotherapeutic targets by genomic profiling of rectal NET metastases. (1st November 2016) - Koşaloğlu, Zeynep; Zörnig, Inka; Halama, Niels; Kaiser, Iris; Buchhalter, Ivo; Grabe, Niels; Eils, Roland; Schlesner, Matthias; Califano, Andrea; Jäger, Dirk
ABSTRACT: Neuroendocrine tumors (NETs) of the gastrointestinal tract are a rare and heterogeneous group of neoplasms with unique tumor biology and clinical management issues. While surgery is the only curative treatment option in patients with early stage NETs, the optimal management strategy for patients with advanced metastatic NETs is unknown. Based on the tremendous success of immunotherapeutic approaches, we sought to investigate such approaches in a case of metastatic rectal NET. Here, we apply an integrative approach using various computational and experimental methods to explore several aspects of the tumor–host immune interactions for immunotherapeutic options. Sequencing of six different liver metastases revealed a quite homogenous set of mutations, and further analysis of these mutations for immunogenicity revealed few neo-epitopes with pre-existing T cell reactivity, which can be used in therapeutic vaccines. Staining for immunomodulatory proteins and cytokine profiling showed that the immune setting is surprisingly different, when compared to liver metastases of colorectal cancer for instance. Taken together, our results highlight the broad range and complexity of tumor–host immune interaction and underline the value of an integrative approach.